Development of a Network Equipment Room Access Notification System Using Facial Recognition Technology - หล่อนิล ณัฐพล; ใยโพธิ์ทอง เอกสิทธิ์; งามดี วุฒิชัย (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This study focuses on the development of a notification system for monitoring access to a network equipment room by utilizing facial recognition technology. The system effectively records entry and exit data without relying on traditional manual logging methods. It integrates various devices such as surveillance cameras and motion sensors, and operates in conjunction with IoT technologies and the LINE application. Real-time notifications, including text messages and photos of personnel entering or exiting the room, are sent through the LINE platform, ensuring comprehensive and convenient access monitoring. The experimental results indicate that the system efficiently records and notifies access events, offering ease of data retrieval and review. Especially with the integration of LINE, administrators can monitor access anytime and anywhere. User satisfaction evaluations revealed a high level of satisfaction, suggesting that the system is suitable for implementation in environments that require secure and efficient access control.